RANCANG BANGUN APLIKASI PENGENALAN BATIK TULIS PASEBAN BERBASIS ANDROID - erik Kurniadi; Rika Nugraha (NUANSA INFORMATIKA, 2021)
There is a lot of useful information about batik culture, such as its history, the philosophical meaning of its motifs, to the development of the batik industry. However, knowledge about batik culture, especially in Paseban batik, is still poorly understood by the wider community, especially the Kuningan community itself. Based on the above background, the authors are interested in conducting research with the title "Application Design for Introduction to Android-Based Paseban Written Batik". Information systems are currently being developed using the WEB platform so as to increase ease of access. By taking advantage of these conditions, it is necessary to develop a method of disseminating information that provides batik knowledge that will be loaded on an Android-based mobile device. This study aims to increase knowledge and insight, instill a love of batik culture, and for the younger generation to continue to maintain and preserve this cultural heritage. The research of this batik material will be specified in Paseban Batik, which is batik produced from Cigugur Kuningan. Keywords: Android, WEB, Batik Tulis Paseban